Effect of increasing levels of rice polishings on ruminal dry matter degradability and productive performance of fattening sheep - Salinas-Chavira, J.; P?rez, J. A.; Rosales, J. A.; Hern?ndez, E. A.; La O, Oreste (Cuban Journal of Agricultural Science, 2013)
he objective of this study was to evaluate the parameters of ruminal degradation and behavior in fattening ovine fed highly concentrated diets with increasing levels of rice polishing. Two experiments were developed: 1.- effects of increasing levels of rice polishing (RP) on ruminal degradability of dry matter (RDDM) and 2.- behavior of fattening ovine. Three diets or treatments were used with equal content of CP (14 %) and metabolizable energy (8.36 MJ/kg of DM). The RP contents in diets were 0 % (T1 or control), 11 % (T2) and 22 % (T3). The RDDM was determined in Pelibuey sheep, using ruminal cannulas. Bags with food samples were incubated in the rumen during 4, 8, 12, 24 and 48 h. Sheep (75 % Pelibuey x 25 % Doper) of 20 ?2.99 kg at the beginning were used for the test of fattening behavior, randomly distributed in individual cages with the same treatments of the RDDM test. Degradation parameters show that the diet with 22 % of RP had higher values in the rapidly soluble fraction (a), as well as the DM which disappeared from the rumen in the 4, 8 and 12 h of incubation. In respect to the control diet, the diet with 22 % of RP had lower ruminal degradability of the soluble fraction (b) and the DM disappeared from the rumen after 48 h of incubation. The potential degradability (a + b) and the constant degradation (c) were not affected by the RP level. Effective degradability at the rumen turnover rate (k) from 5 to 10 % was higher in the diet with 22 % of RP. The highest daily food intake for the behavior test was for sheep in T3 and the lowest in T2 (P < 0.05). The biggest daily gain in sheep was in the control group and the lowest in the T2 group (P < 0.05). The best feed conversion was observed in the control group and the lowest in T3 group (P < 0.05). It can be concluded that the RP, at high concentrated portions, can increase the RDDM and the rate of ruminal fluid, and can affect the behavior in sheep fattening. However, the RP reduces the most expensive conventional ingredients such as soybean, sorghum grain and cattle bait. Key words: rice by-product, ovine fattening, ruminal kinetics.